Tony Harrison and the Holocaust - Rowland, Antony (Liverpool English texts and studies ;, 2001)
This book argues that Tony Harrison?s poetry is barbaric. It revisits one of the most misquoted passages of twentieth-century philosophy: Theodor Adorno?s apparent dismissal of post-Holocaust poetry as?impossible? or?barbaric?. His statement is reinterpreted as opening up the possibility that the awkward and embarrassing poetics of writers such as Harrison might be re-evaluated as committed responses to the worst horrors of twentieth-century history. Most of the existing critical work on Harrison focuses on his representation of class, which occludes his interest in other aspects of historio.